Anthropology and law confronted with child health: an integrated approach (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
The article reflects on how, in societies that are becoming increasingly multicultural, the concept of health should be understood in an anthropological key, including the minority in the evaluation of what is psycho-physical well-being. The article starts from a juridical reconstruction of the rights that come into play in balancing and shows how the idea of health – currently understood as the psycho-physical well-being of the individual – is an idea culturally located in the West and can be enriched by other conceptions (medical pluralism). The article therefore focuses on the analysis of a series of cultural and religious practices in which the health of the minor has come to the fore, some now well known in the jurisprudence (blood transfusion prohibition, male and female circumcision), others still ignored in the Italian debate (cupping and gua sha).
Keywords: Traditional medicine; gua sha; cupping; blood transfusion; multiculturalism